HALLIDAY'S DISCOURSE ANALYSIS IN ONLINE MEDIA COMMUNICATION AT ISLAMIC BOARDING SCHOOLS - Kun Wazis; Ahmad Hayyan Najikh; Muhammad Nurul Fadillah (Indonesian Journal of Islamic Communication, 2023)
The development of the danger of the corona virus disease (Covid-19) outbreak throughout the world and in Indonesia is increasing and has a wide impact. The Indonesian government issued a presidential decree (Keppres) which stipulates Covid-2019 as a type of disease that causes public health emergencies and must be overcome. During 2020, The online media of Islamic Boarding Schools in East Java that are in the Red Zone, namely Malang, Jember, Lumajang, and Situbondo display news and information related to Covid-19 vigilance. Three online media pesantrennuris.net, mubakid.or.id, and sukorejo.com represent Islamic boarding schools online media in reporting pesantren communications in the fight against Covid-19. For this reason, descriptive qualitative research using the Halliday Model Discourse analysis is considered The results of the pesantren communication research displayed through online media found three important things. First, the social action of pesantren in tackling Covid-19 lies in the kiai's message which must be obeyed by all pesantren residents. Two, strict regulations relating to the handling of Covid-19 in Islamic boarding schools. Third, the language style of the online media of the three pesantren displays the journalistic style of pesantren. appropriate by researchers because there are three important dimensions to be explored, namely the field of discourse, the tenor of discourse, and the mode of discourse. Based on this research, it further strengthens that Islamic boarding schools as institutions of social change have been proven to have a very large contribution to the intellectual life of the nation and must get support from various parties in the context of preventing the spread of Covid-19.